Anthropogenic disturbance promotes the diversification of antibiotic resistance genes and virulence factors in the gut of plateau pikas (Ochotona curzoniae) - Zhao, Yaqi; Zhang, Liangzhi; Tang, Xianjiang; Ren, Shien; Zhang, Yanming (Frontiers in Ecology and Evolution, 2022)
The prevalence and transmission of antibiotic resistance genes (ARGs) and virulence factors (VFs) pose a great threat to public health. The importance of pollution in determining the occurrence of ARGs and VFs in wildlife is poorly understood. Using a metagenomic approach, this study investigates the composition and functional pathways of bacteria, ARGs, and VFs in the gut microbiome of Plateau pikas in regions of medical pollution (MPR), heavy tourist traffic (HTR), and no contamination (NCR). We found that the abundance of probiotic genera (Clostridium, Eubacterium, Faecalibacterium, and Roseburia) were significantly lower in the HTR. The metabolic pathways of replication and repair in the endocrine and nervous systems were significantly enriched in the MPR, whereas endocrine and metabolic diseases were significantly enriched in the NCR. The Shannon and Gini–Simpson α-diversity indices of ARGs were highest in the HTR, and there were significant differences in β-diversity among the three regions. The resistance of ARGs to glycopeptide antibiotics increased significantly in the MPR, whereas the ARGs for aminocoumarins increased significantly in the HTR. The diversity of mobile genetic elements (MGEs) was significantly higher in the MPR than in other regions. We observed a strong positive correlation between ARGs and pathogenic bacteria, and the network structure was the most complex in the MPR. There were significant differences in the β-diversity of VFs among the three regions. Medical pollution led to significant enrichment of fibronectin-binding protein and PhoP, whereas tourism-related pollution (in the HTR) led to significant enrichment of LPS and LplA1. Our study indicates that environmental pollution can affect the structure and function of gut microbes and disseminate ARGs and VFs via horizontal transmission, thereby posing a threat to the health of wild animals.